Pneumatic drying of cassava starch: Numerical analysis and guidelines for the design of efficient small-scale dryers. Issue 4 (12th March 2017) - Chapuis, A.; Precoppe, M.; Méot, J. M.; Sriroth, K.; Tran, T.
ABSTRACT: In a number of tropical countries, the expansion of cassava processing is tied to the development of small-scale, energy-efficient pneumatic dryers used to dry flour and starch. To facilitate this development, in this study a model of the pneumatic drying of starch particles was developed, to be fitted to measurements taken from large cassava processing factories. After that, numerical simulations were performed to analyze the effects of geometry and operating conditions on the energy efficiency and pipe length required to dry the product. The results clarified the influence of processing capacity, air inlet conditions, and starch particle size, emphasizing that air velocity as well as the dilution of the starch should be minimized. In light of the findings described here, we offer guidelines for the design of efficient small-capacity flash dryers.